Purple as a plum - Dingles, Molly; Velez, Walter (Sea Girt, N.J. : Dingles & Co. ; Bethany, Mo. : Distributed by Gumdrop Books, 2004)
Simple text and illustrations introduce the color purple and objects that bear that color.
Keywords: Purple; Color; Purple; Color